Pathophysiology concepts of altered health states - Porth, Carol Mattson (Lippincott Williams & Wilkins, 2009)
Emphasizes "concepts" of altered health states, as opposed to factual descriptions of diseases and disorders. By taking this physiologic approach, this title ensures a comprehension of the whole of body function.